Strategi dan Hambatan Manajemen Pengelolaan Lembaga Pendidikan Anak Usia Dini - Eka Eka; Siti Nor Asiah; Livita Magfiratul Laili (Program Pascasarjana Universitas Pesantren Tinggi Darul Ulum (Unipdu) Jombang, 2022)
This study aims to determine the strategies implemented by Early Childhood Education (PAUD) institutions, especially the Integrated Islamic Kindergarten (TKIT) Plus Al-Hidayah Tenggarong in implementing student management. This study also aims to determine the obstacles experienced in the implementation of student management. This is a field research conducted using a qualitative method with a descriptive approach. This study will describe the strategies used by TKIT Plus Al-Hidayah Tenggarong in the implementation of student management, and also describe the obstacles experienced in the implementation of student management. Data collection techniques used in this study were observation, interviews, and documentation. The results of this study indicate that student management can be a forum to improve the quality of child development. TKIT Plus Al-Hidayah Tenggarong carries out a coaching strategy to improve the ability of students through small preachers (d?‘?) and ?u?? prayers in congregation before carrying out learning and memorizing daily prayers and short suras that are easy to memorize. The obstacle experienced is that student management programs, especially the little dai program, are difficult to implement because the development of each child is different, and the frequent change of teachers also makes it difficult to manage students.